RANCANG BANGUN BETTY PET SHOP DENGAN LAYANAN PET HOTEL BERBASIS WEB - Syahrizal Adindaputra Sudarmono; Fivi Syukriah; Erlina Erlina (Jurnal Ilmiah Teknik, 2022)
Pets provide us with entertainment as we go about our daily lives. Bathing, eating, and fun activities for animals to keep them entertained are all necessary to keep pets clean and healthy.Due to limited time and busyness, animal owners are not always able to be close to their pets, and as a result, they are unable to care for these animals, so they require a place and means of care, as well as care for their beloved animals.This pet hotel website was designed to make it easier for owners to order day care and care for their beloved pets without regard for space or time constraints.This website was created with UML (Unified MarkUp Language). he SDLC (Software Development Life Cycle) method was used to build this website, which includes the stages of analysis, design, manufacture, and testing. This website was built with JavaScript, PHP, and MySQL.